2020
DOI: 10.1111/jonm.12991
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the influence of workplace violence and bystander behaviour on patient safety in Korea: A pilot study

Abstract: Aims To explore the influences of clinical nurses’ workplace violence and bystander behaviour on patient safety. Background Bystanders’ role in social violence affects the consequences of said violence; however, few studies have explored the relationship between workplace violence and patient safety among nurses working in clinical settings. Methods A cross‐sectional survey design was conducted using a structured questionnaire pertaining to workplace violence, bystander behaviour, patient safety culture and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 42 publications
3
19
0
1
Order By: Relevance
“…Contextual factors associated with personal harassment were consistent with previous research 9 . Although most situations involved other nursing professionals, the experiences also included other individuals (eg, patients, family, physicians).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Contextual factors associated with personal harassment were consistent with previous research 9 . Although most situations involved other nursing professionals, the experiences also included other individuals (eg, patients, family, physicians).…”
Section: Discussionsupporting
confidence: 80%
“…In keeping with other research, individuals experiencing personal or bystander harassment reported lower job satisfaction and perceived their work environments as more tolerant to harassment. 8,9,13 These findings underscore the importance of examining both personal and bystander harassment of nurses and the incidents of these events. Contextual factors associated with personal harassment were consistent with previous research.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…A recent survey of 4263 nurses in the healthcare industry showed that 54% of respondents had experienced verbal violence by patients [ 2 ], including negative emotional behaviors exhibited by patients, such as anger, swearing, insults, yelling, and speaking rudely toward nurses; all of these are part of a phenomenon known as “mistreatment by patients” [ 3 ]. These behaviors not only reduce nurses’ work productivity and job performance [ 4 , 5 ] and hinder patient safety [ 6 ], but also may affect their own mental health and long-term development. More specifically, mistreatment by patients may directly threaten nurses’ positive attitudes toward their work and careers, which can hinder their career success [ 7 ].…”
Section: Introductionmentioning
confidence: 99%